Characterization of Farming System and Determinants of Adoption of Horticultural Enterprises in Achham, Nepal - Dhital, Pankaj Raj; Ojha, Ganapati; Dhakal, Shiva Chandra; Devkota, Naba Raj (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
Nepal's rural agriculture is characterized by its diverse and interconnected system of farming. The Ghaghara/Karnali river system in the northwest of Nepal represents the typical rural farming system. A study was conducted in 2019 in the Mid-hill district of Achham, Nepal in the same river system with the aim of studying the farming system, its features, and different factors that influence the horticultural enterprise adoption by the farmers. A total of 130 respondents were selected from the Panchadewal Binayak Municipality of Achham district of Nepal using the multi-stage purposive random sampling approach. Beside the characteristics of Farming system; various factors that determine the horticultural enterprise adoption were examined using the binary logit regression model. The integrated or multi-enterprise farming system was found to be dominated by three primary enterprises: horticulture, livestock, and agronomy. The pattern of household participation in each enterprise under study was substantially the same, with almost three fourth of the household choosing main grain crops, and horticultural crops especially vegetables; around 85% adopting livestock in an integration system, and only about 13% fruit trees. The study demonstrated that among the many factors under inquiry, the gender of household head, size of the family and visit by the extension workers influences the farmer’s decision on adoption of horticultural enterprise significantly. Though non-significant, age, level of education, farming experience, agriculture as primary occupation and credit facilities also positively plays the role in decision of horticultural enterprise adoption. Ethnicity, years of residence in same location, dependency ratio, total land size, training and visit to extension worker were negatively associated with farmers' decisions regarding horticulture enterprises. Thus, for the development of agriculture in rural areas with a higher adoption of horticultural enterprise which as higher potentialities in the rural agricultural system in Nepal, it is necessary to consider the role of various socioeconomic and personality variables in farmers decision to adopt the type of farm enterprise.